2016
DOI: 10.25011/cim.v39i6.27496
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neurofeedback therapy in healthy young subjects

Abstract: Effects of neurofeedback therapy in healthy young subjects Abstract Purpose: Neurofeedback refers to a form of operant conditioning of electrical brain activity, in which desirable brain activity is rewarded and undesirable brain activity is inhibited. The research team aimed to examine the efficacy of neurofeedback therapy on electroencephalogram (EEG) for heart rate, electrocardiogram (ECG) and galvanic skin resistance (GSR) parameters in a healthy young male population.Methods: Forty healthy young male subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…The improvement of clinical symptoms of anxiety and depression is also crucial in preventing relapse in cocaine- and heroin-abstinent patients (Corominas et al, 2010; DiGirolamo et al, 2017; Hasin et al, 2002). The current results are in line with a previous study reporting that the Othmer method was useful in restoring sympathetic imbalance in the general population (Altan et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…The improvement of clinical symptoms of anxiety and depression is also crucial in preventing relapse in cocaine- and heroin-abstinent patients (Corominas et al, 2010; DiGirolamo et al, 2017; Hasin et al, 2002). The current results are in line with a previous study reporting that the Othmer method was useful in restoring sympathetic imbalance in the general population (Altan et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…It should be noted that the control group also showed changes in brain connectivity, indicating that the Sham-Neurofeedback cannot be assumed to be a completely neutral condition (see also the discussion in MMAT Quality Assessment). Altan et al (2016) observed an increased Beta activity and diminished alpha activity in the qEEG parameters during and after a single ILF-Neurofeedback session, highlighting the role of ILF-Training in restoring the neurovegetative balance. These studies suggest that objective changes occur in brain activity as a result of ILF-Neurofeedback training.…”
Section: Infra-low Neurofeedback and Brain Activitymentioning
confidence: 81%
“…Altan et al ( 2016 ) observed an increased Beta activity and diminished alpha activity in the qEEG parameters during and after a single ILF-Neurofeedback session, highlighting the role of ILF-Training in restoring the neurovegetative balance. These studies suggest that objective changes occur in brain activity as a result of ILF-Neurofeedback training.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations